Poster: A Safe and Responsible Work Life in NZ Dairy Farming - Rhodes, Deborah (New Zealand Journal of Health and Safety Practice, 2024)
A Master of Health Research Pilot: Workplace Health and Safety at Victoria University of Wellington, used the Nordic Occupational Safety Climate Questionnaire (Kines, 2011) for the first time in a NZ industry. It was undertaken in dairy milking sheds, and determined the workgroup had low perceptions of safety. It followed with interviews of owner/managers, answering safety-based questions from domains of the NOSACQ-50. The findings and discussion formed the basis for PhD research.